Physicochemical properties of the tacaco (Sechium tacaco) fruit (UNED Research Journal, 2026)
Introduction: Tacaco (Sechium tacaco) is an autochthonous Costa Rican fruit (Cucurbitaceae) restricted to its unprocessed consumption. Its poorly studied physicochemical properties limit its industrialization. Objective: To characterize the physical and chemical properties of the tacaco fruit. Methods: We studied 192 ripe tacaco fruits from Cervantes and Paraiso in Cartago, Costa Rica. We measured 32 samples of at least 100g of edible fraction. All chemical analyses were by AOAC methods. Results: The fruits had an average mass of 38g, of which 59% corresponded to the edible fraction. Tacaco is similar to other cucurbits in its high moisture and low-fat content, corresponding to 79% and 0.22 g/100 g, respectively. However, its relatively higher protein content (0.95 g/100 g), total carbohydrates (16.75 g/100 g), and dissolved solids (7.00 °Brix) stand out. Average moisture was 79%, whereas ash and fiber contents were 0.79 g/100 g and 0.78 g/100 g, respectively. The fruit is slightly acidic, and its dissolved solids content indicates intermediate sweetness (coefficient of variation below 10% for both variables). Conclusion: This fruit has a low-fat content and relatively higher percentages of protein and carbohydrates compared to other cucurbits, which may confer nutritional value that could be exploited in the development of innovative food products.
Keywords: autochthonous vegetable; endemic; nutritional composition; cucurbit; food